Hormone Use, Reproductive History, and Risk of Lung Cancer. Issue 7 (July 2015) - Schwartz, Ann G.; Ray, Roberta M.; Cote, Michele L.; Abrams, Judith; Sokol, Robert J.; Hendrix, Susan L.; Chen, Chu; Chlebowski, Rowan T.; Hubbell, F. Allan; Kooperberg, Charles; Manson, JoAnn E.; O'Sullivan, Mary Jo; et al.
<x xml:space="preserve">Abstract</x> Introduction: Results from the Women's Health Initiative clinical trials demonstrated no increase in the risk of lung cancer in postmenopausal women treated with hormone therapy (HT). We conducted a joint analysis of the Women's Health Initiative observational study data and clinical trials data to further explore the association between estrogen and estrogen-related reproductive factors and lung cancer risk. Methods: Reproductive history, oral contraceptive use, and postmenopausal HT were evaluated in 160, 855 women with known HT exposures. Follow-up for lung cancer was through September 17, 2012; 2467 incident lung cancer cases were ascertained, with median follow-up of 14 years. Results: For all lung cancers, women with previous use of estrogen plus progestin of less than 5 years (hazard ratio = 0.84; 95% confidence interval = 0.71–0.99) were at reduced risk. A limited number of reproductive factors demonstrated associations with risk. There was a trend toward decreased risk with increasing age at menopause (ptrend = 0.04) and a trend toward increased risk with increasing number of live births (ptrend = 0.03). Reduced risk of non–small-cell lung cancer was associated with age 20–29 years at first live birth. Risk estimates varied with smoking history, years of HT use and previous bilateral oophorectomy. Conclusions: Indirect measures of estrogen exposure to lung tissue, as used in this study, provide only weak evidence for an association between reproductive history or HT use and risk of lung cancer. More detailed mechanistic studies and evaluation of risk factors in conjunction with estrogen receptor expression in the lung should continue as a role for estrogen cannot be ruled out and may hold potential for prevention and treatment strategies.